2016
DOI: 10.1071/rd14294
|View full text |Cite
|
Sign up to set email alerts
|

Localisation and endocrine control of hyaluronan synthase (HAS) 2, HAS3 and CD44 expression in sheep granulosa cells

Abstract: The aim of the present study was to investigate the hormonal regulation of hyaluronan (HA) components in sheep granulosa cells. HA components are present in the reproductive tract and have a range of physical and signalling properties related to reproductive function in several species. First, abattoir-derived ovaries of sheep were used to determine the localisation of HA synthase (HAS) 1–3 and CD44 proteins in antral follicles. Staining for HAS1–3 and CD44 proteins was most intense in the granulosa layer. Acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 61 publications
1
4
0
Order By: Relevance
“…The abundance of CD44 in porcine GCs has already been confirmed as well, and the parallel relation between the amount of hyaluronic acid and CD44 expression has been indicated [27]. Since the study conducted by Chavoshinejad et al revealed that IGF1, combined with other factors such as oestradiol, gonadotropins or insulin, stimulated CD44 expression in ovine GCs [28], we conclude that this may be the case in our study, as we observed upregulation of both of these genes.…”
Section: Discussionsupporting
confidence: 85%
“…The abundance of CD44 in porcine GCs has already been confirmed as well, and the parallel relation between the amount of hyaluronic acid and CD44 expression has been indicated [27]. Since the study conducted by Chavoshinejad et al revealed that IGF1, combined with other factors such as oestradiol, gonadotropins or insulin, stimulated CD44 expression in ovine GCs [28], we conclude that this may be the case in our study, as we observed upregulation of both of these genes.…”
Section: Discussionsupporting
confidence: 85%
“…Knockout studies in mice showed that Has2 −/− embryos lack HA, resulting in embryonic lethality during mid-gestation 10 11 . HAS2 has a close relationship with ovary development and function, and is predominantly located in the GC layers of rat and sheep ovaries 5 12 . Knockdown of CCAAT-enhancer-binding protein CEBβ decreases the HAS2 mRNA level and results in the arrest of pGCs at S phase of the cell cycle, indicating that HAS2 plays an important role in GC function 13 .…”
mentioning
confidence: 99%
“…In mammals, HAS2 is regulated by multiple factors such as hormones, transcription factors, and epigenetic factors 17 18 19 . In GCs, follicle-stimulating hormone (FSH) stimulates HAS2 expression 12 and affects downstream events of the HAS2-HA-CD44-Caspase-3 pathway such as HA synthesis, CD44 expression, and Caspase-3 expression and activity 4 17 . Transcription factors such as CREB1, RAR, SP1, SP3, and YY1 regulate HAS2 expression by binding to functional binding sites within the HAS2 promoter region 20 .…”
mentioning
confidence: 99%
“…Some factors are known to affect HAS2 expression. Estradiol can stimulate HAS2 mRNA expression when combined with insulin-like growth factor-1, insulin, and follicle-stimulating hormone ( Chavoshinejad et al ., 2016 ). The TGF-β/Smad4 signaling pathway can activate the HAS2-HA system ( Li et al ., 2020 ).…”
Section: Discussionmentioning
confidence: 99%